The Educational Inspection, organizational intelligence and leadership, taking into account the development of the European Education Area 2030 and the data from the Teaching and Learning International Survey, TALIS. - Alcañiz Miñano, Vicente (Avances en Supervisión Educativa, 2024)
The article analyzes the 2030 European Education Area strategic framework and the main findings provided by the OECD Teaching and Learning International Survey, in relation to teaching work and school management, which are the two factors that most affect the quality of education and student results. All of this to contextualize the situation of lack of definition of the educational inspection and how its intelligence and organizational culture and its leadership capacity can influence in a very positive way in improving the quality of Education.